2013
DOI: 10.1177/1524500413483456
|View full text |Cite
|
Sign up to set email alerts
|

“Wow, That Was Funny”

Abstract: In this study, we examined whether or not exposure to a humorous surround campaign in Iowa (United States) could produce a multiplicative effect based on Intermedia Theory. Until You're Ready, AvoidtheStork.com © was designed to prevent unintended pregnancies among young women. In the case of unintended pregnancy, interpersonal sharing is important because women's contraceptive decisions are influenced by what others, including their friends, think about the health issue. In a sample of college students (n ¼ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Positively valenced information should be more widely shared, because it can enhance positive images of senders (Alhabash, et al, 2013; Kim et al, 2013). The role of positive emotions in the form of humor (Campo, et al, 2013; Shifman, 2012) and pride and empathy (van den Hooff, Schouten, & Simonovski, 2012) predict transmission measured through intentions as well as behaviors. Along the same lines, Berger and Milkman (2012) found that positive news articles invited more frequent email-based retransmissions than those with negative emotional valence.…”
Section: Message or Information Factorsmentioning
confidence: 99%
“…Positively valenced information should be more widely shared, because it can enhance positive images of senders (Alhabash, et al, 2013; Kim et al, 2013). The role of positive emotions in the form of humor (Campo, et al, 2013; Shifman, 2012) and pride and empathy (van den Hooff, Schouten, & Simonovski, 2012) predict transmission measured through intentions as well as behaviors. Along the same lines, Berger and Milkman (2012) found that positive news articles invited more frequent email-based retransmissions than those with negative emotional valence.…”
Section: Message or Information Factorsmentioning
confidence: 99%
“…Nanin, Bimbi, Grov, and Parsons (2009) reported that 40% of those aware of the Stop the Sores campaign reported that the ads made them want to talk to friends about syphilis, with this number higher among men of color. Campo et al (2013) found that humor is conducive to sharing, with respondents who found an unplanned pregnancy prevention campaign to be more humorous more likely to share the campaign. Similarly to Reder (1997), Campo et al (2013) found that women were more likely to have shared the campaign with others than men.…”
Section: Sharingmentioning
confidence: 98%
“…Campo et al (2013) found that humor is conducive to sharing, with respondents who found an unplanned pregnancy prevention campaign to be more humorous more likely to share the campaign. Similarly to Reder (1997), Campo et al (2013) found that women were more likely to have shared the campaign with others than men. Thus, it appears from both experimental research and evidence from campaign evaluations that humorous messaging can promote sharing of messages as well as interpersonal discussions about the message and health topic.…”
Section: Sharingmentioning
confidence: 98%
See 2 more Smart Citations